Research on Dynamic Response of Slopes With Weak Interlayers Under Mining Blasting Vibration - Zhang, Xiaochao; Yang, Qingwen; Pei, Xiangjun; Du, Ruifeng (Frontiers in Energy Research, 2022)
As blasting technology starts to be used in a wide range of areas, blast loading has led to an increasing number of geological disasters such as slope deformation, collapses, and soil slippage. Slopes with weak interlayers are more likely to be deformed and damaged under the influence of blast loading. It is of great importance to study the evolution for the deformation of slopes with weak interlayers during blasting excavation. This study constructed a slope model with a weak interlayer to investigate the influence of different factors of blasting, including explosive charge, blast radius, blast origin, and multi-hole blasting, on the internal dynamic response. The deformation mechanism of slopes with weak interlayers under the influence of blast loading was analyzed. Test results show that each layer of the model had a different displacement response (uncoordinated dynamic response) to blasting with various factors. Explosive energy and the pattern of dynamic response of each layer varied depending on different settings of blasting factors such as explosive charge, blast radius, blast origin, and detonation initiation method. When the explosive energy produced under the influence of various factors was small, the change in the uncoordinated dynamic response between layers was significant, and the change gradually became less significant as the explosive energy increased. Therefore, this study has proposed the concept of critical explosive energy, and it is speculated that when the explosive energy produced with various factors is less than critical explosive energy, the dynamic response is mainly affected by the internal structure of the slope (property difference induced geologic layers). In other words, the uncoordinated motion of material’s particles in each layer is caused by different limitations and the degree of movement of the particles, which leads to the uncoordinated dynamic response and uncoordinated deformation of each layer. If the explosive energy is greater than the critical value, the dynamic response of each layer is mainly affected by the explosive energy. The differences in the internal structure of the slope are negligible, and the incoordination of dynamic responses between layers gradually weakens and tends to synchronize.